Comparison Of Legal Reasoning Models In Consideration Of Decision No. 064/G/2014/PTUN SMG, NO. 135/B/2015/PT.TUN.SBY, And No. 99/PK/TUN/2016 In The Case Of Pt Semen Gresik (Persero) Tbk Environmental Permit In Rembang Regency, Central Java - Hery Dwi Utomo; Absori Absori; Kachippa Suvirat; Khudzaifah Dimyati; Kelik Wardiono; Saepul Rochman (Jurnal Jurisprudence, 2023)
ABSTRACT  Purpose of the study: This study aims to understand the lawsuit of the Samin Community in Rembang Regency against Governor's Decree No. 660.1/17/2012, which permits the development and exploitation of natural resources in the Kendeng Mountains. This dispute not only shows a lawsuit but, more broadly, is the counter-hegemonic movement between local law and national law, which is marked by the victory of the Samin Community at the level of Judicial Review at the Supreme Court. Methodology: The research was carried out through observation, interview, and literature review to explain local and national legal disputes, which were analyzed qualitatively using legislation, unwritten law, and the Gramsci Counter Hegemony approach. Results: The study revealed that: first, local law disputes against national law in Rembang Regency occurred because of the dominance of national law over local law, which recognizes indigenous people only when stated in the law. Second, the Samin Indigenous people still adhere to traditions, myths, and ecological principles called Saminism, which only allow them to farm and serve as a cultural identity. Therefore, they may not be able to survive if they have another profession. Third, the judge's decision in the form of a caliph on earth is influenced by the soul of the mother earth community of the Samin Community and forms a new norm so that it becomes a new hegemony against national law. Application of the study: This research can be used by law enforcers so that their legal decisions rely on not only legal positivism values but also transcendental local legal concepts. Novelty/Originality of research: No previous research has linked the dispute over permits for constructing a cement factory in the Rembang Regency and Decision No. 99/PK/TUN/2016 with a counter-hegemonic approach and transcendental-based local laws. Keywords: legal comparison, legal reasoning, environmental law, court judgment   ABSTRAK  Tujuan Kajian: Kajian ini bertujuan untuk memahami gugatan masyarakat Samin di Kabupaten Rembang terhadap Keputusan Gubernur No. 660.1/17/2012 yang mengizinkan pembangunan dan ekspolitasi sumber daya alam di pegunungan Kendeng. Sengketa ini tidak hanya menunjukan gugatan hukum namun yang lebih luas adalah gerakan kontra hegemoni antara hukum lokal dengan hukum nasional yang ditandai dengan kemenangan masyarakat Samin pada tingkat Peninjauan Kembali di Mahkamah Agung. Metodologi: Penelitian dilaksanakan dengan melakukan observasi, wawancara, dan kajian literatur yang dimaksudkan untuk menjelaskan sengketa hukum lokal dan nasional yang dianalisis secara kualitatif dengan menggunakan perundang-undangan, hukum tidak tertulis dan pendekatan Kontra Hegemoni Gramsci. Hasil-hasil: Hasil Penelitian ini menunjukan bahwa pertama, Sengketa hukum lokal melawan hukum nasional di Kabupaten Rembang terjadi karena adanya dominasi hukum nasional atas hukum lokal yang hanya mengakui masyarakat adat hanya jika disebutkan oleh Undang-Undang. Kedua, masyarakat Adat Samin masih berpegang pada tradisi, mitos dan prinsip-prinsip ekologis yang disebut Saminisme yang yang hanya mengizinkan mereka untuk bertani saja dan sebagai identitas budaya, sebab itu mereka tidak mungkin mampu bertahan hidup apabila berprofesi lain; dan Ketiga, Amar putusan hakim berupa khalifah di muka bumi dipengaruhi oleh jiwa masyarakat ibu bumi masyarakat Samin dan membentuk norma baru sehingga menjadi hegemoni baru melawan hukum nasional. Aplikasi Kajian: Penelitian ini dapat digunakan bagi penegak hukum agar putusan hukumnya tidak hanya bersandar pada nilai-nilai positivisme hukum, namun juga konsep hukum lokal yang bersifat transendental. Kebaruan/Originalitas Penelitian: Belum ada penelitian sebelumnya yang menghubungkan sengketa izin pembangunan Pabrik Semen di Kabupaten Rembang dan putusan No. 99/PK/TUN/2016 dengan pendekatan kontra hegemoni dan hukum local berbasis transendental. Katakunci : Perbandingan Hukum, Penalaran Hukum, Hukum Lingkungan, Putusan Pengadilan